PSYCHOEDUCATION GET OUR FUTURE: OPTIMIZING THE ROLE OF PARENTING EDUCATION IN IMPROVING MENTAL HEALTH LITERACY OF CHILDREN WITH DISABILITIES - Yudowati, Kristin Afriyani; Suwari, Suwari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to optimize the role of parenting education in improving mental health literacy of children with disabilities. Through the psychoeducation program